2014
DOI: 10.1007/s00776-014-0561-z
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of pin tract infection with iodine-supported titanium pins

Abstract: Background Pin tract infection is one of the most common complications of external fixation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 22 publications
0
19
0
Order By: Relevance
“…An innovative technology using iodine to produce porous anodic oxide implant surfaces with the antiseptic properties of iodine was studied in a prospective uncontrolled cohort study for both prophylaxis in high risk patients, and for treatment in confirmed MSK infection cases . Confirmatory reports on subsets of these patients with hip replacement implants or fixator pins reported no hip implant infections and decreased pin tract infections respectively …”
Section: Resultsmentioning
confidence: 99%
“…An innovative technology using iodine to produce porous anodic oxide implant surfaces with the antiseptic properties of iodine was studied in a prospective uncontrolled cohort study for both prophylaxis in high risk patients, and for treatment in confirmed MSK infection cases . Confirmatory reports on subsets of these patients with hip replacement implants or fixator pins reported no hip implant infections and decreased pin tract infections respectively …”
Section: Resultsmentioning
confidence: 99%
“…The reported incidence of external fixation infection was 3–80% according to different diagnostic criteria . Risk factors for acquiring pin‐tract infections include patient factors (advanced age or smoking) and external fixator parameters (prolonged duration or types of pin) . Various methods, such as regular cleansing with different solutions and specific dressings, have been applied to prevent infections .…”
Section: Discussionmentioning
confidence: 99%
“…The biological half-life of an antibiotics coating or silver coating is said to be only several hours or days [ 15 , 16 ]. On the other hand, recent data showed that the amount of iodine on the titanium pin in patients with external fixation was maintained, with approximately 40% remaining after 1 year [ 17 ]. Fifth, iodine-supported implants have excellent osteoconduction and good biocompatibility [ 11 ]; bone conduction is reportedly not possible on certain materials such as silver [ 10 ].…”
Section: Discussionmentioning
confidence: 99%